A Two-Way Interfacial Condition for Lattice Simulations (Advances in Applied Mathematics and Mechanics, 2010)
In this paper, we formulate a two-way interfacial condition for simulating lattice dynamics in one space dimension.With a time history treatment, the incoming waves are incorporatedinto the motion of the boundary atoms accurately. This conditionreduces to the absorbing boundary condition when there is noincoming wave. Numerical tests validate the effectiveness of theproposed condition in treating simultaneously incoming waves andoutgoing waves.